2014
DOI: 10.14198/jhse.2014.9.proc1.05
|View full text |Cite
|
Sign up to set email alerts
|

Personality characteristics and its effect on performance in the race BMX

Abstract: Hřebíčková, S., Pacholík, V. & Mach, J. (2014). Personality characteristics and its effect on performance in the race BMX. J. Hum. Sport Exerc., 9(Proc1), pp.S245-S248. The aim of this study was to describe personality characteristics of top athletes -10 elite bicross (BMX) racers (18+ years), both men and women. For our research we used SPARO test -monitoring of basal psychical autoregulation of personality, which was evaluated with t-test. Particular segments were compared with population and with top athlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Although it could be considered that combat can lead to aggressive or impulsive behaviors, athletes of combat sports showed lower scores for general impulsiveness, as similar studies have shown (Parthi, 2013; Gronek et al, 2015). Other studies have indicated that practitioners of endurance sports (e.g., BMX, open water swimming, and triathlon) dispose of higher impulsiveness indicators (Monasterio, 2013; Hřebícková et al, 2014). Moreover, our sample showed inverse correlation scores between functional perfectionism and general impulsiveness.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although it could be considered that combat can lead to aggressive or impulsive behaviors, athletes of combat sports showed lower scores for general impulsiveness, as similar studies have shown (Parthi, 2013; Gronek et al, 2015). Other studies have indicated that practitioners of endurance sports (e.g., BMX, open water swimming, and triathlon) dispose of higher impulsiveness indicators (Monasterio, 2013; Hřebícková et al, 2014). Moreover, our sample showed inverse correlation scores between functional perfectionism and general impulsiveness.…”
Section: Discussionmentioning
confidence: 98%
“…Team and endurance sports athletes had the highest scores in dysfunctional resources. The literature on sports psychology, focused on disorders or alterations in behaviors, has shown that for training in this kind of sport, it helps to have high scores in perfectionism and low self-regulation (Hřebícková et al, 2014; Gouttebarge et al, 2015b; Nixdorf et al, 2016; Prinz et al, 2016).…”
Section: Discussionmentioning
confidence: 99%